Utilization of Single and Double Orifice Plates in Pipe Inner Flow Structure by Computational Method - Ridwan Daris Naufal; James Julian; Fitri Wahyuni; Riki Hendra Purba; Nely Toding Bunga (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2025)
The orifice plate is a device that disrupts the flow in the pipe. The disturbed flow results in the formation of flow structures. The flow structure formed can be utilized for several applications such as multi-fluid mixing and microbubble generator. Using orifice plates to utilize the flow structure results in more significant pressure loss. This study aims to identify the characteristics of the flow structure generated by single and double orifice plates with 1D and 2D spacing at various Reynolds numbers, namely Re = 1×104, 5×104, 1×105, and 5×105, as a basis for application in these various applications. The results show that single and double orifice plates can produce flow structure phenomena such as recirculation and vortex regions. The recirculation area is formed smaller in the double orifice plate due to the flow that is separated faster to converge back to the pipe wall but broader so that the flow of the orifice plate is narrower. Increasing the applied Reynold's number causes the separated flow to reconnect to the pipe wall faster, resulting in a smaller recirculation area. Double orifice plates are more suitable for applications that require a certain degree of mixing or pressure distribution, but with a consequent more significant pressure loss. Meanwhile, single plates can be used for simple needs with little pressure loss.